2021
DOI: 10.1111/pala.12541
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic biomechanics underpins the evolutionary success of trilobites

Abstract: Arthropods (i.e. insects, spiders, crustaceans, myriapods and others), are the most successful Phanerozoic animals. The group is characterized by the possession of a segmented body, jointed limbs and a hard cuticle that is episodically moulted. One highly successful but now extinct group of arthropods is the trilobites. Trilobites underwent episodic moulting (ecdysis), and most trilobites possess facial sutures, lines of weakness in the cephalon, via which the exuviae is shed and the animal emerges. However, z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The position of facial sutures corresponded to a trade‐off between burrowing and moulting, and could be an advantage for developing an infaunal lifestyle (Esteve et al . 2021). The presence of spines is identified as contributor to overall morphological variation for pygidia too, for which elongation (sag.)…”
Section: Discussionmentioning
confidence: 99%
“…The position of facial sutures corresponded to a trade‐off between burrowing and moulting, and could be an advantage for developing an infaunal lifestyle (Esteve et al . 2021). The presence of spines is identified as contributor to overall morphological variation for pygidia too, for which elongation (sag.)…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a more simplistic approach, applying FEA on plane structures proved to be a valuable tool to reveal differences in stress patterns between the head shapes of Pheidole workers. We suggest a more widespread application of this approach in other animal lineages for instances where 3D structures are too complex to allow the simultaneous investigation of many species (Esteve et al, 2021;Fletcher et al, 2010;Pierce et al, 2008Pierce et al, , 2009Rayfield, 2004Rayfield, , 2005.…”
Section: Current Evidence Suggests That the Geographic Distribution Ofmentioning
confidence: 99%
“…We aimed to investigate the relationship between head shape and biomechanical performance by finite element analysis (FEA) (Kupczik, 2008;Rayfield, 2007) in Pheidole worker plane head shapes. Although a simplistic perspective, the use of 2D data in biomechanical simulations proved to be effective as a first approximation to the mechanical demands of complex structures (Marcé-Nogué et al, 2013), as demonstrated for the effects of biting behavior in crocodilians (Pierce et al, 2008(Pierce et al, , 2009, theropods (Rayfield, 2005) and Tyrannosaurus rex (Rayfield, 2004) skulls, as well as bite loading in vertebrate jaws (Deakin et al, 2022) and the mechanical consequences of borrowing on the trilobite cephalic region (Esteve et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However the presence of dorsal sutures in earlier diverging artiopodans such as Acanthomeridion (Hou et al, 2017a; Du et al, 2019) in combination with the fusion of sutures during ontogeny for some trilobites (Drage et al, 2018), the lack of a clear link between morphology and moulting behaviour (Drage, 2022) and alternative functional demands on the location of sutures in trilobites (e.g. to facilitate burrowing, Esteve et al, 2021); have called this view into question. Alternative possibilities are that dorsal sutures had a deep root within the clade, and were subsequently lost in some artiopodans and multiple times within Trilobita, or that a facial suture was acquired independently at least twice in Artiopoda (Hou et al, 2017a; Du et al, 2019).…”
Section: Introductionmentioning
confidence: 99%